Shanghai girls a novel - See, Lisa. (New York : Random House Large Print, 2009)
In the mid 1930's two well-educated sisters from Shanghai go to Los Angeles to become brides of the "Gold Mountain men" when their family is on the verge of bankruptcy. When the get their they are detained, interrogated, and humiliated for months. When one of the sisters becomes pregnant they vow that no one will ever know.
Keywords: Sisters -- Fiction; Chinese -- United States -- Fiction; Immigrants -- United States -- Fiction; Family secrets -- Fiction; Large type books; Domestic fiction